2005
DOI: 10.4161/cc.4.11.2146
|View full text |Cite
|
Sign up to set email alerts
|

Regulated Separation of Sister Centromeres depends on the Spindle Assembly Checkpoint but not on the Anaphase Promoting Complex/Cyclosome

Abstract: Key to faithful genetic inheritance is the cohesion between sister centromeres that physically links replicated sister chromatids and is then abruptly lost at the onset of anaphase. Misregulated cohesion causes aneuploidy, birth defects and perhaps initiates cancers. Loss of centromere cohesion is controlled by the spindle checkpoint and is thought to depend on a ubiquitin ligase, the Anaphase Promoting Complex/Cyclosome (APC). But here we present evidence that the APC pathway is dispensable for centromere sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
80
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(84 citation statements)
references
References 40 publications
4
80
0
Order By: Relevance
“…71) could also arrest somatic cells in the M-phase upon proteasome inhibition upstream from both Nek2A and cyclin B proteolysis. Recently, Giménez-Abián et al 72 provided evidence that in mammalian cells anaphase could occur in the presence of non-degraded cyclin B and securin. More interestingly, they showed that some non-identified substrates of proteasome which regulate mitotic progression are degraded in mammalian cells in APC/C-independent manner.…”
Section: Discussionmentioning
confidence: 99%
“…71) could also arrest somatic cells in the M-phase upon proteasome inhibition upstream from both Nek2A and cyclin B proteolysis. Recently, Giménez-Abián et al 72 provided evidence that in mammalian cells anaphase could occur in the presence of non-degraded cyclin B and securin. More interestingly, they showed that some non-identified substrates of proteasome which regulate mitotic progression are degraded in mammalian cells in APC/C-independent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Any error in this process may result in aneuploid embryo formation, which causes early embryo death, spontaneous abortion and genetic diseases. 55,56 Central to the accurate segregation is the assembly of a specific site for microtubule attachment, the kinetochore, on each sister chromatid. 57 The centromeric chromatin is essential for the formation of a functional kinetochore in all eukaryotes.…”
Section: Discussionmentioning
confidence: 99%
“…4A, bottom), excluding the possibility that Cdc14B Δ/Δ cells initially presented with a mitotic exit defect that was silenced over time through compensatory mechanisms. Because timely completion of anaphase and mitotic exit require the APC-dependent degradation of securin and cyclin B, 2,28 we examined the patterns of securin and cyclin B turnover in wildtype and Cdc14B Δ/Δ cells, as well as auto-cleavage of the cysteine protease separase, which is normally inhibited by securin and cyclin B. All three anaphase-specific proteolytic events occurred normally in Cdc14B Δ/Δ cells (Fig.…”
Section: © 2 0 0 8 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%